Antioxidants from Malaysian agarwood (Aquilaria spp.) leaf extracts and their applications in in vitro model and food system - Tay, Pei Yin (2015)
Agriculture by-products are undervalued substrates that are normally removed and disposed from the food production line. In this study, young leaves from three commercial species of Malaysian agarwood (Aquilaria malaccensis, Aquilaria subintegra and Aquilaria crassna) were examined. These are by-products from agarwood plantations and are usually discarded during the cultivation of agarwood trees. The first part of the present study assessed the effects of the ethanol concentration (0-100%) (v/v), solid-to-solvent ratio (1:10-1:60) (w/v) and extraction time (30-180 min) on the extraction of polyphenols from young agarwood leaves. The total phenolic content (TPC), total flavonoid content (TFC) and DPPH radical-scavenging capacity were used for the quantification of polyphenols, and assessment of antioxidant capacity. The appropriate ranges of the extraction parameters were determined through single-factor experiments, and the optimal conditions for polyphenol extraction were established through response surface methodology (RSM). Among the three species of young agarwood leaves, the extract from A. subintegra young leaves (ASE) obtained through extraction with 64.64% (v/v) ethanol and a solid-to-solvent ratio of 1:70 (w/v) for 120 min was selected for the second part of the study. The antioxidative interactions (synergy,additive and antagonism) between ethanolic ASE and α-tocopherol were evaluated through assays of the DPPH radical-scavenging activity, the β-carotene bleaching system and liposome peroxidation. Among all of the combinations of ASE and α-tocopherol, only fraction 1/3 showed a synergistic interaction, which agrees well with the results from three different assays. In the third part of this study, ASE was incorporated into soybean oil-based mayonnaise at a concentration of 1/3 relative to the tocopherol content to prevent its deterioration during storage. The peroxide value (POV), total oxidation value (TOTOX) and conjugated trienes (CT) of ASE-enriched mayonnaise were significantly (p < 0.05) lower than the negative control mayonnaise samples at the end of the storage period. The addition of ASE to mayonnaise presented comparable ability to protect against deterioration compared with the addition of the commercially available synthetic ethylenediaminetetraacetic acid (EDTA). ASE was further tested for its toxicity via brine shrimp lethality and hemolytic analyses. Low brine shrimp lethality and low hemolytic activity with IC50 values of 96.6 μg/mL and 1864.7 μg/mL against brine shrimp and human erythrocytes, respectively, were observed. In addition, the major bioactive compound in ASE, namely iriflophenone 3-C-β-glucoside (4.1%, w/w) with an IC50 of 54.5 mg/L for scavenging DPPH radicals was identified and quantified based on 1D NMR, 2D-NMR, LC-MS and UV-vis spectral data. In summary, this study may serve as a reference for future natural polyphenol applications in the food industry.